SOCIO-RELIGIOUS RELATION BETWEEN THE HILL TRIBES AND THE GHAMARA SATRA OF LAKHIMPUR DISTRICT OF ASSAM –A CASE STUDY OF PRE-INDEPENDENT PERIOD. - Sumanta Das (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Present Ghamara Satra is located about 5k.M. from North Lakhimpur town According to the Charit Puthi of the Gharmara was established by Shankarisan, a Brahman of Kanouj in 1216 at Sadiya under the patronize of the Chutia King. After the fall Chutia kingdom the Satra was transferred to Present Dhenukhana, Machkhowa of Dhemaji district of Assam. During the Burmese invasion the Satra again shifted to the present location. At that time the neighbor hill tribes of the Satras were such as Nyishi (Daphalas), Hill-Miris, Abors, Galos and the Apatanis. It was one and only Satras benefitted from the offerings of the Ahom and the Chutia king . At first phase the Satra was followed Vedas but later on the Satra was inspired by Neo-Vaishnavism propagated by Srimanta Sankardev. During the Ahom reign period there was not seen more relation between the hill tribes and the Gharmara Satra. But during the colonial period especially from the early 19th century, Gharmara Satra propagated not only ritual of Vaisnavism but also propagate education, awareness against the superstition among the hill tribes inhabited at Kimin, Johing, Siajuli, Passighat and Dollungmukh of Arunachal Pradesh. The present paper has attempted to highlight the role of Gharmara Satra to propagate the Neo- Vaishnavism and social reforms among the hill tribes like Nyishi, Hill-Miris, Apatanis and the Adis of Arunachal Pradesh.